Homocsytein, vitamine B12 and folic acid levels in major depression patients treated with fluoxetine or S-citalopram - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
Introduction: Elevated homocystein take place in degenerative processes like dementia and cardiovascular diseases. But, the relation between depression and homocysteine is still being investigated. It is long known that deficiency of folic acid or Vitamine B12 may cause depression. It is in fact difficult to interprete the role of homocystein in depression since the deficiency states of these substances also produce elevated homocystein levels. The aim of this study is to show the effect of major depression and its treatment in the levels of homocystein, folic acid and Vitamine B12. Methods: Thirty one female volunteer patients aged between 18-45 years who were diagnosed as major depression and to be treated either with fluoxetine or s-citalopram were enrolled into the study. Sixteen healthy female controls were also included in the study. 17 patients received s-citalopram (10 mg/day) and 14 received fluoxetine (20 mg/day). Hamilton Depression Scale and Beck Suicide Inventory were performed and blood samples were taken. These tests were also repeated in the second psychiatric evaluation. The median period between 2 psychiatric visits is 11 days. Results: Analysis of variance was applied to to compare the basal levels and post-treatment values. Comparison of folic add values measured in healthy controls, pre- and post-treatment values of patients did not yield a statistically significant difference (p=0,86). Similarly no significance was observed for Vitamine B12 values (p=0,93). Homocsytein values were found to be different in patients and healthy controls(p=0,046), where the levels were lower in the healthy controls than that of the patients. But the levels of homocystein were not found to be statistically different before and after treatment. Conclusion: There are some report about a correlation between elevated levels of homocsytein and depression. Our study inconsistent with the findings of earlier studies; however some studies also stated that there is no relation between homocystein and depression. The reason that we did not observe any change after treatment may be the early sampling (median 11 days). Nevertheless, it is not true to expect a change following SSRI treatment, since elevation of homocystein may imply the ongoing defect in the monoamine metabolism. There is no doubt that newer treatment approaches that are directed to correct the monoamine metabolism according to the ethiopatagenesis of depression will give more promissing results.
Keywords: Major Depression; homocysteine; folic add; Vitamine B12; fluoxetine; s-citalopram; HOMOCYSTEINE; FOLATE; DISEASE; DEFICIENCY; SERUM